Comparative Neuroprotective Effects of Dexamethasone and Minocycline during Hepatic Encephalopathy - Maha Gamal; Zainab Abdel Wahab; Mohamed Eshra; Laila Rashed; Nivin Sharawy (Neurology Research International)
Objective. Encephalopathy and brain edema are serious complications of acute liver injury and may lead to rapid death of patients. The present study was designed to investigate the role of the inflammatory mediators and oxidative stress in the cytotoxic brain oedema and the neuroprotective effects of both minocycline and dexamethasone. Methods. 48 male albino rats were divided into 4 groups: control group, acute liver injury (ALI) group, minocycline pretreated ALI group, and dexamethasone pretreated ALI group. 24 hours after acute liver injury serum ammonia, liver enzymes, brain levels of heme oxygenase-1 gene, iNOS gene expression, nitrite/nitrate, and cytokines were measured. In addition, the grades of encephalopathy and brain water content were assessed. Results. ALI was associated with significant increases in all measured inflammatory mediators, oxidative stress, iNOS gene expression, and nitrite/nitrate. Both minocycline and dexamethasone significantly modulated the inflammatory changes and the oxidative/nitrosative stress associated with ALI. However, only minocycline but not dexamethasone significantly reduced the cytotoxic brain oedema. Conclusion. Both minocycline and dexamethasone could modulate inflammatory and oxidative changes observed in brain after ALI and could be novel preventative therapy for hepatic encephalopathy episodes.